The rating of reduce the loss of heat energy in multi-family building as a result of the thermomodernization - Jarosz-Hadam, Monika; Fic, Stanisław (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
In the article, the impact of supply and exhaust mechanical ventilation with the recovery on reduce the demand for thermal energy in an apartment building was analyzed. Also examined was the impact of the type of an external thermal insulation on distribution of temperature and pressure in the partition. The calculation was made using Purmo OZC 6.0 software for a historic building, 3-storey, which will undergo a deep thermomodernization. Based on the calculations it was found that the type of the insulation do not affect in a significant way to a heat loss through the baffle, and only affects the thickness of the baffle. The greatest reduction in the energy demand occurs in the result of the application of the mechanical ventilation in the building. Analysis of the loss shows that the traditional ventilation systems produce large heat losses at the level of 46.9%. The calculations have shown that supply and exhaust mechanical ventilation with the heat recovery reduces the heat loss ratio to the level of 26.5%.